1947
DOI: 10.1097/00000658-194709000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Omphalomesenteric (Vitelline) Artery Causing Intestinal Obstruction and Gangrene of Meckelʼs Diverticulum

Abstract: AMONG THE RARER CONDITIONS which are encountered in surgery those which precipitate practical problems are especially worthy of consideration. Persistent omphalomesenteric, or vitelline, artery falls into this category. Its presence is one of the infrequent causes of intestinal obstruction. The literature contains only i6 cases in which a persistent omphalomesenteric artery caused symptoms, and, of this number, evidence of intestinal obstruction was found at operation or autopsy in ii cases (69 per cent). In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1949
1949
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 1 publication
1
20
0
Order By: Relevance
“…We reported a patulous artery within the cord uncovered by peritoneum, attaching the Meckel's diverticulum to the ileal mesentery. Its incidence being 32% as reported by previous authors 3 The first case of persistent omphalomesenteric artery was reported by Sandifort in 1777. Meckel, in 1809, reported a case ,and was the first writer to suspect the true origin of this condition.…”
Section: Discussion and Embryological Basismentioning
confidence: 56%
See 3 more Smart Citations
“…We reported a patulous artery within the cord uncovered by peritoneum, attaching the Meckel's diverticulum to the ileal mesentery. Its incidence being 32% as reported by previous authors 3 The first case of persistent omphalomesenteric artery was reported by Sandifort in 1777. Meckel, in 1809, reported a case ,and was the first writer to suspect the true origin of this condition.…”
Section: Discussion and Embryological Basismentioning
confidence: 56%
“…1 It is well to know, however that it may be one of the underlying causes of intraabdominal pathology that one may occasionally encounter. 3 From the review of literature analysis of above case report, the surgeon must always bear in mind the possibility that Meckel's diverticulum with a persistent omphalomesenteric artery may be the aetiological factor in any acute abdominal emergency,especially when specific diagnosis is difficult. The present paper will highlight the embryological basis and related clinical implications of the Meckel's diverticulum with persistent artery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The foregut gives rise to the first portion of the duodenum, while the hindgut derives the last one‐third of the transverse colon, the descending and sigmoid colon. By the 6th week, the yolk sac and yolk stalk disappear, along with the vitelline arteries (Manning and McLaughlin, 1947).…”
Section: Developmental Anatomymentioning
confidence: 99%